Tibial Torsion and Ankle Arthritis: Is External Tibial Rotation Associated with Varus Deformity in Patients with Ankle Arthritis?. Issue 4 (22nd October 2020) - Barber, Collin C.; Hall, Teresa; Madden, Tyler; Kothari, Parin D.; LaPointe, Monica; Anderson, John G.; Bohay, Donald R.; Maskill, John D.; Padley, Michelle A.
Category: Ankle; Ankle Arthritis; Hindfoot Introduction/Purpose: The effect of tibial torsion on lower extremity mechanical alignment has been well studied in the literature, including its effect on lower extremity osteoarthritis. It has been suggested that external tibial torsion is associated with cavus hindfoot deformity and may lead to varus osteoarthritis of the ankle. To our knowledge, there are no studies investigating this relationship. The purpose of this study is to characterize the relationship of tibial torsion with ankle coronal plane deformity in patients with ankle arthritis. Methods: The study is a retrospective, cohort of 223 patients who have undergone total ankle arthroplasty at a single institution. Preoperative computerized tomography was used to measure tibial torsion and coronal deformity. Descriptive statistics and regression analysis were used to analyze the data. Results: Descriptive analysis of all 223 patients demonstrated a maximum of 23.9 degrees varus and 20.5 degrees valgus among all patients. The mean for varus deformity was 6.86 degrees with a standard deviation of +- 6.39. Tibial rotation was calculated at an average of 20.8 degrees external rotation, with a maximum of 15.2 degrees internal rotation and 59.5 degrees external rotation in all patients. Plotting overall coronal ankle tilt versus tibial torsion revealed overall varus deformity with R2 of 0.016. Regression analysis of all varus deformities against external tibial torsion revealed a R2 of 0.02. Varus deformity 1 standard deviation above the mean against external tibial torsion demonstrated a R2 of 0.072. Valgus deformity against external tibial torsion revealed a R2 of 6.75 x10-5. Conclusion: An association between external tibial torsion and varus ankle arthritis has been proposed in the literature. The results of our study did not show an association between tibial torsion and coronal deformity in ankle arthritis in all patients undergoing total ankle arthroplasty at our institution. A difference may exist in certain subgroups, such as patients with neuromuscular disorders, but further investigation will be necessary to determine this relationship.